Оцінка вразливостей систем, побудованих по технології інтернет речей за методикою CVSS - Ліхота, О. І. (ХНУРЕ, 2020)
The purpose of my work was to analyze the vulnerabilities that can occur in any device using Internet technology. An analysis of the threats that were detected in the device, such as the ThingsPro Suite the IIoT gateway and device manager from the company Moxa, was carried out. After analysis, the risk of information security was calculated using the CVSS methodology.
Keywords: CVSS; ThingsPro Suite; виконання довільного коду; вразливість систем